Experimental Study of Joint Roughness Influence on Fractured Rock Mass Seepage. (28th February 2021) - Tian, Zhongxi; Dai, Chunquan; Zhao, Qingshuang; Meng, Zhaobo; Zhang, Baoliang
Abstract : Surrounding rock pressure, water pressure, and joint roughness are the important factors that affect the fractured rock mass seepage. It is of great significance to quantify the influence of these factors through experiments. In this study, rock fracture joint surfaces were measured. Next, 3D coordinates of joint surfaces were extracted with using the Geomagic software, and joint roughness was described using the mean variance of protrusion height and equidistant fluctuation angle, which were acquired through calculation. Stress-seepage coupling test was then conducted on the samples on a triaxial apparatus, and the effects of confining stress and water pressure on the permeability of single-fracture rock were investigated. On the basis of the relationship between the parameters in data fitting expression and the mean variance of protrusion height and equidistant fluctuation angle, the calculation formula of the permeability coefficient including joint roughness, confining pressure, and seepage pressure difference was derived.